Redesign of The Gobis Surabaya Mobile Application User Interface Based on User Experience Evaluation To Enhance User Understanding and Features Using The User-Centered Design Method - Anang Pramono; Alvin Bakri (Pelopor Publikasi Akademika, 2024)
The Gobis Surabaya application, developed by the Surabaya City Government, provides public transportation information. The Transportation Agency aims to facilitate transportation access through this application. The development process includes data collection, analysis, design, implementation, testing, and maintenance. This research describes the redesign efforts of the GOBIS Surabaya mobile application interface using UCD to enhance user experience. From an analysis of 30 respondents using the System Usability Scale (SUS), it was found that the previous application had low usability. However, after a meticulous redesign process, the SUS score significantly improved, with the majority of respondents rating it above 85, indicating a substantial increase in usability. The redesign process involved careful consideration of user needs. Usability testing conducted by Maze also confirmed excellent UI and UX quality. With usability scores ranging from 97 to 100, no incomplete tasks, click accuracy from 0% to 4.5%, and task completion times ranging from 1.5 to 24.4 seconds, the testing showed high efficiency levels. Overall, the testing results affirmed that the UI and UX design provided a satisfying user experience, indicating user satisfaction with the application. It is expected that this research will facilitate users in utilizing the GOBIS Surabaya application.